Proyecto de tratamiento urbano integral de la ronda hídrica del caño gramalote de la ciudad de Villavicencio (2022)
The present degree work is a proposal for an urban project, which is developed within the City and Environment line, in the subcategory of sectoral urban design, called "Integral Urban Treatment Project of the Caño Gramalote water round located in t of Villavicencio.